IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI KEGIATAN MUHADLARAH DI PONDOK PESANTREN BAITUL ARQOM - Berlian Dwi Elita Sari; Fadlillah Fadlillah (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
Objective: This study aims to analyze the implementation of character education through muhadlarah activities at Baitul Arqom Islamic Boarding School, particularly in developing students’ self-confidence and discipline, as well as identifying the role of administrators and teachers (ustadz/ustadzah) in the guidance process. Methods: This research employed a qualitative approach with a field research design. Data were collected through in-depth interviews, participant observation, and documentation. The informants consisted of the boarding school caretaker, teachers, administrators, and students who actively participated in muhadlarah activities. Data were analyzed using data reduction, data display, and conclusion drawing techniques. Results: The findings indicate that regular and structured muhadlarah activities effectively enhance students’ self-confidence through public speaking practice, preparation of speech materials, and the courage to express ideas. Additionally, these activities improve students’ discipline through punctual attendance, independent task preparation, and adherence to rules. Administrators and teachers play a significant role in providing guidance, motivation, supervision, and evaluation throughout the process. Novelty: This study highlights the integration of religious-based extracurricular activities with character education, demonstrating that muhadlarah serves as an effective and practical medium for strengthening self-confidence and discipline among students in Islamic boarding school settings.